1997
DOI: 10.1099/0022-1317-78-11-2779
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of pestivirus infection in cell culture by envelope proteins E(rns) and E2 of classical swine fever virus: E(rns) and E2 interact with different receptors.

Abstract: Pure preparations of envelope glycoproteins E rns and E2 of classical swine fever virus (CSFV) synthesized in insect cells were used to study infection of porcine and bovine cells with the pestiviruses CSFV and bovine viral diarrhoea virus (BVDV). Almost 100 % inhibition of infection of porcine kidney cells with CSFV was produced by 100 µg/ml E rns . After removal of the virus no E rns was needed in the overlay medium (growth medium) to maintain this level of inhibition. In contrast, 100 % inhibition of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 36 publications
9
96
0
1
Order By: Relevance
“…However, very little is known about the role of glycosylation in the function of pestivirus glycoproteins. A previous study that examined the closely related pestivirus BVDV E2 glycoprotein expressed in a baculovirus/insect cell system (26) showed that the pattern of glycosylation affects the ability of the isolated glycoprotein to prevent infection of calf testis cells with BVDV, an otherwise inhibitory effect observed with wildtype E2 protein (14). The same study also showed that modification of N1 and N3 sites in BVDV E2 impaired expression and secretion of the protein in insect cells, suggesting that glycosylation at those sites is essential for correct folding and subsequent secretion of E2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, very little is known about the role of glycosylation in the function of pestivirus glycoproteins. A previous study that examined the closely related pestivirus BVDV E2 glycoprotein expressed in a baculovirus/insect cell system (26) showed that the pattern of glycosylation affects the ability of the isolated glycoprotein to prevent infection of calf testis cells with BVDV, an otherwise inhibitory effect observed with wildtype E2 protein (14). The same study also showed that modification of N1 and N3 sites in BVDV E2 impaired expression and secretion of the protein in insect cells, suggesting that glycosylation at those sites is essential for correct folding and subsequent secretion of E2.…”
Section: Discussionmentioning
confidence: 99%
“…E2 is the most immunogenic of the CSFV glycoproteins (15,40,44), inducing neutralizing antibodies and protection against lethal CSFV challenge. E2 has been implicated, along with E rns (14) and E1 (43), in viral adsorption to host cells; indeed, chimeric pestiviruses exhibit infectivity and cell tropism phenotypes consistent with those of the E2 gene donor (18,40). Modifications introduced into these glycoproteins appear to have an important effect on CSFV virulence (21,29,31,41).…”
mentioning
confidence: 99%
“…The genome consists of a single open reading frame, which is translated into a polyprotein that is co-and post-translationally cleaved into structural and non-structural proteins (Rümenapf et al, 1993). The structural proteins comprise the nucleocapsid C protein and three envelope glycoproteins, E rns , E1 and E2, of which at least E rns and E2 are postulated to be responsible for virus attachment and/or cell entry (Donis & Dubovi, 1987;Hulst & Moormann, 1997). E1 is assumed to function as a membrane anchor for E2 (Rümenapf et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…E2 is considered essential for CSFV replication, as virus mutants containing partial or complete deletions of the E2 gene are nonviable (7). E2 has been implicated, along with E rns (8) and E1 (9), in viral adsorption to host cells (10,11). Modifications introduced into this glycoprotein appear to have an important effect on CSFV virulence (12)(13)(14)(15)(16).…”
Section: Importancementioning
confidence: 99%